Three-Dimensional Matrix-Induced Autologous Chondrocytes Implantation for Osteochondral Lesions of the Talus: Midterm Results. (17th April 2012) - Magnan, B.; Samaila, E.; Bondi, M.; Vecchini, E.; Micheloni, G. M.; Bartolozzi, P.
Abstract : Introduction . We evaluate the midterm results of thirty patients who underwent autologous chondrocytes implantation for talus osteochondral lesions treatment. Materials and Methods . From 2002 to 2009, 30 ankles with a mean lesion size of 2, 36 cm 2 were treated. We evaluated patients using American Orthopaedic Foot and Ankle Surgery and Coughlin score, Van Dijk scale, recovering time, and Musculoskeletal Outcomes Data Evaluation and Management System. Results . The mean AOFAS score varied from 36.9 to 83.9 at follow-up. Average of Van Dijk scale was 141.1. Coughlin score was excellent/good in 24 patients. MOCART score varied from 6.3 to 3.8. Discussion . This matrix is easy to handle conformable to the lesion and apply by arthroscopy. No correlation between MRI imaging and clinical results is found. Conclusions . Our results, compared with those reported in literature with other surgical procedures, show no superiority evidence for our technique compared to the others regarding the size of the lesions.